Association of eating patterns and abdominal adiposity in Brazilian - Pereira, Kelly Aparecida da Cunha; Segheto, Wellington; Ferreira, Fabrícia Geralda; Segheto, Kátia Josiany; Longo, Giana Zarbato; Silva, Danielle Cristina Guimarães da (Revista de Nutrição, 2017)
To examine the relationship between dietary patterns and abdominal adiposity among adults living in the urban area of Viçosa, Minas Gerais, Brazil. A population-based, cross-sectional study of 959 adults of both sexes. Information on sociodemographic characteristics and dietary intake was collected through questionnaires. Abdominal adiposity was evaluated using waist circumference and the anthropometric indices waist-to-hip ratio and waist-to-height ratio. Food patterns were identified by factor analysis. Poisson regression was used for multivariate analysis. Abdominal adiposity was identified by waist circumference in 59.06% (95%CI=52.77–65.08) of the sample, by waist-to-hip ratio in 54.65% (95%CI=47.92–61.21), and by waist-to-height ratio in 9% (95%CI=54.61–69.03). Two dietary patterns, named as traditional Brazilian and bar, were identified in the sample, but only the latter was statistically associated with abdominal adiposity determined by the three parameters. The study identified two eating patterns in the population, a healthy and an unhealthy pattern, the latter being associated with greater odds of abdominal adiposity. Thus, it is important to take measures to reverse this trend.

Explorar a relação entre padrões alimentares e a adiposidade abdominal entre adultos residentes na área urbana do município de Viçosa, Minas Gerais. Estudo transversal, de base populacional, realizado com 959 indivíduos adultos e de ambos os sexos. Foram coletadas informações sobre as características sociodemográficas e de consumo alimentar por meio de questionários. Para avaliação da adiposidade abdominal, avaliou-se o perímetro da cintura e os índices antropométricos relação cintura/quadril e relação cintura/estatura. Os padrões alimentares foram identificados por análise fatorial. Para análise multivariada, foi utilizada regressão de Poisson. A adiposidade abdominal identificada pela perímetro da cintura foi de 59,06% (IC95%=52,77–65,08), pela relação cintura/quadril foi de 54,65% (IC95%=47,92–61,21) e pela relação cintura/estatura de 62,09% (IC95%=54,61–69,03). Foram identificados dois padrões alimentares, nomeados de padrão “tradicional” e “bar”, sendo que somente o último padrão foi estatisticamente associado à adiposidade abdominal determinada pelos três parâmetros. A população do estudo apresentou dois padrões alimentares, um considerado saudável e outro não saudável, o qual foi associado à maior chance de adiposidade abdominal. Sendo assim, medidas que revertam tais situações são importantes de serem adotadas.
Keywords: Factor analysis; Feeding behavior; Obesity abdominal; Análise fatorial; Comportamento alimentar; Adiposidade abdominal